2022
DOI: 10.2174/1570159x19666210909150200
|View full text |Cite
|
Sign up to set email alerts
|

Identifying c-fos Expression as a Strategy to Investigate the Actions of General Anesthetics on the Central Nervous System

Abstract: : Although general anesthetics have been used in the clinic for more than 170 years, the ways in which they induce amnesia, unconsciousness, analgesia, and immobility remain elusive. Modulations of various neural nuclei and circuits are involved in the actions of general anesthetics. The expression of the immediate early gene c-fos and its nuclear product, c-fos protein can be induced by neuronal depolarization; therefore, c-fos staining is commonly used to identify the activated neurons during sleep and/or wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 174 publications
0
2
0
Order By: Relevance
“…Neuronal extracellular stimulation typically results in the elevation of adenosine 3’,5’-cyclic monophosphate (cAMP) levels and calcium influx, ultimately leading to the upregulation of immediate early genes (IEGs) such as c-fos ( Yap and Greenberg, 2018 ; Morgan and Curran, 1989 ). The translation product of c-fos, c-Fos protein, offers single-cell spatial resolution and has been utilized as a biomarker to identify anesthetic-activated brain regions ( Zhang et al, 2022 ). Previous investigations of c-Fos expression throughout the brain demonstrated that GABAergic agents inhibited cortical activity while concurrently activating subcortical brain regions, including VLPO, median preoptic nucleus (MEPO), lateral septal nucleus (LS), Edinger-Westphal nucleus (EW), and locus coeruleus (LC; Smith et al, 2016 ; Lu et al, 2008 ; Yatziv et al, 2020 ; Han et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal extracellular stimulation typically results in the elevation of adenosine 3’,5’-cyclic monophosphate (cAMP) levels and calcium influx, ultimately leading to the upregulation of immediate early genes (IEGs) such as c-fos ( Yap and Greenberg, 2018 ; Morgan and Curran, 1989 ). The translation product of c-fos, c-Fos protein, offers single-cell spatial resolution and has been utilized as a biomarker to identify anesthetic-activated brain regions ( Zhang et al, 2022 ). Previous investigations of c-Fos expression throughout the brain demonstrated that GABAergic agents inhibited cortical activity while concurrently activating subcortical brain regions, including VLPO, median preoptic nucleus (MEPO), lateral septal nucleus (LS), Edinger-Westphal nucleus (EW), and locus coeruleus (LC; Smith et al, 2016 ; Lu et al, 2008 ; Yatziv et al, 2020 ; Han et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the review by Platholi and Hemmings [ 5 ], the authors review the cellular and molecular mechanisms of transient and persistent general anesthetic alterations of synaptic transmission and plasticity, which is critically important to higher-order brain functions such as learning and memory in general anesthesia. For the review by Donghang Zhang et al [ 6 ], c-fos staining is commonly used to identify the activated neurons during sleep and/or wakefulness, as well as in various physiological conditions in the central nervous system. Identifying c-fos expression is also a direct and convenient method to explore the effects of general anesthetics on the activity of neural nuclei and circuits.…”
mentioning
confidence: 99%